Cost analysis of dermal allograft patch utilization in rotator cuff repair - Adrik Z. Da Silva, BS; Joshua Mizels, MD; Christopher E. Clinker, BS; Minkyoung Yoo, PhD; Richard Nelson, PhD; Christopher Joyce, MD; Robert Z. Tashjian, MD; Peter N. Chalmers, MD (JSES Reviews, Reports, and Techniques)
Background: To perform an analysis of intraoperative costs associated with arthroscopic rotator cuff repair (RCR) acellular dermal allograft patch augmentation and interposition. Methods: This was a matched cohort retrospective cost identification analysis. We identified patients who underwent arthroscopic RCR with acellular dermal allograft patch augmentation or interposition between 2014 and 2023 at a single academic center. These were matched based on age and tear size to a cohort of patients who underwent arthroscopic RCR without a patch. Patients without preoperative MRI data were excluded. Via chart review, we collected demographics, medical comorbidities, tear characteristics, and intraoperative repair characteristics. Patch and control patients were compared with paired t tests. Differences in costs between patch and control patients were assessed using multivariable regression controlling for observable covariates. Results: One hundred and thirty-two (132) total patients were included: 66 patch patients and 66 control patients. The patch group demonstrated more tear retraction and utilized single row medial repair more frequently. Multivariable analysis revealed that there was a $4930 total direct cost increase with the utilization of a patch (P <.001) after controlling for age, body mass index, American Society of Anesthesiologists (ASA), Charlson comorbidity index, gender, surgeon, tear width, number of anchors, occupation, biceps treatment, prior surgery, and repair construct. The multivariable analysis also revealed that a higher ASA was associated with a $1440 increase in cost (P =.012). Biceps tenotomy was associated with a $3303 decrease in cost compared to tenodesis (P =.001). Additionally, single row medial repair demonstrated a $1745 decrease in total direct cost when compared to a double row repair construct (P =.019). Conclusion: The addition of a patch increases the total direct cost by $4930 when compared to arthroscopic RCR without a patch. Increased ASA, biceps tenodesis, and use of a double row repair construct were also associated with increased cost.